PENGARUH VARIASI SUDUT NOZZLE TERHADAP KECEPATAN PUTAR TURBIN DAN DAYA OUTPUT PADA PROTOTYPE PLTMH MENGGUNAKAN TURBIN TURGO - I Putu Bayu Suka Yasa; I Wayan Arta Wijaya; I Gusti Ngurah Janardana (Program Studi Teknik Elektro UNUD, 2022)
Turgo turbine is an impulse turbine that uses a water drop height (head), the ability of the runner rotational speed of a turgo turbine is influenced by the following variables the height of the water drop (head), nozzle angle, number of nozzles, and nozzle spray distance, but there are several problems that exist in the turgo turbine, one of wich is at the nozzle there is no equation that determine the nozzle angle to produces maximum output on the turgo turbine so it is need to test the nozzle angle on the turgo turbine, therefore this reasearch was conducted with the aim of knowing the effect of variations in the nozzle angle by using a turgo turbine to produce maximum rotation of the turbine and the highest efficiency at MHP. The quantitative experimental method is carried out by calculating the primary data obtained. Testing the prototype in this study used a nozzle angle variation 65°, 70°, 75° with preassure 21 psi using 18 blades. Based on the research, the best nozzle angle is 70° wich produces 782,8 rpm turbin rotation before coupling and 565,4 rpm after coupling. The generator rotation is 1062,4 before load coupled and 850,2 after load coupled 260 Watts. The voltage without load is 36,126 Volts and 8,296 Volts with a lamp load of 260 Watts. Torque is 0,123 Nm and Efficiency is 1,099% the low the low efficiency value because using a comparison between hydraulic power and the output power of the generator.